Safety for mobile encountered-type haptic devices in large-scale virtual reality - Mortezapoor, Soroosh; Ghazanfari, Mohammad; Vasylevska, Khrystyna; Vonach, Emanuel; Kaufmann, Hannes (Frontiers in Virtual Reality, 2025)
Mobile robots are becoming more common in Virtual Reality applications, especially for delivering physical interactions through Encountered-Type Haptic Devices (ETHD). However, current safety standards and definitions of collaborative robots (Cobots) do not sufficiently address situations where an immersed user shares the workspace and interacts with a mobile robot without seeing it. In this paper, we explore the specific safety challenges of using mobile platforms for ETHDs in a large-scale immersive setup. We review existing robotic safety standards and perform a risk assessment of our immersive autonomous mobile ETHD system CoboDeck. We demonstrate a structured approach for potential risk identification and mitigation via a set of hardware and software safety measures. These include strategies for robot behavior, such as pre-emptive repositioning and active collision avoidance, as well as fallback mechanisms. We suggest a simulation-based testing framework that allows evaluating the safety measures systematically before involving human subjects. Based on that, we examine the impact of different proposed safety strategies on the number of collisions, robot movement, haptic feedback rendering, and noise resilience. Our results show considerably improved safety and robustness with our suggested approach.